To Whistleblow or Not to Whistleblow: Affective and Cognitive Differences in Reporting Peers and Advisors. - McIntosh, Tristan; Higgs, Cory; Turner, Megan; Partlow, Paul; Connelly, Shane; Mumford, Michael D.; Steele, Logan; MacDougall, Alexandra E. (Science & Engineering Ethics, 2019)
Traditional whistleblowing theories have purported that whistleblowers engage in a rational process in determining whether or not to blow the whistle on misconduct. However, stressors inherent to whistleblowing often impede rational thinking and act as a barrier to effective whistleblowing. The negative impact of these stressors on whistleblowing may be made worse depending on who engages in the misconduct: a peer or advisor. In the present study, participants are presented with an ethical scenario where either a peer or advisor engages in misconduct, and positive and the negative consequences of whistleblowing are either directed to the wrongdoer, department, or university. Participant responses to case questions were evaluated for whistleblowing intentions, moral intensity, metacognitive reasoning strategies, and positive and negative, active and passive emotions. Findings indicate that participants were less likely to report the observed misconduct of an advisor compared to a peer. Furthermore, the findings also suggest that when an advisor is the source of misconduct, greater negative affect results. Post-hoc analyses were also conducted examining the differences between those who did and did not intend to blow the whistle under the circumstances of either having to report an advisor or peer. The implications of these findings for understanding the complexities involved in whistleblowing are discussed.